Always in style - Pooser, Doris (London Judy Piatkus (Publishers) Limited, 1987)
Easy-to-follow advice which aims to benefit women who are interested in their appearance and would like to develop their own sense of style.
Includes index.
Keywords: Women's clothing; Clothing and dress; Fashion design